2017
DOI: 10.1188/17.cjon.65-71
|View full text |Cite
|
Sign up to set email alerts
|

Weight Management: Perception, Interest, and Preferences in Adult Cancer Survivors

Abstract: Among 209 respondents who completed the survey, 35% were overweight and 27% were obese. Most participants indicated that they would like to lose weight or were interested or very interested in participating in weight management programs. The results reinforce the need for the oncology team to provide weight management support to cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…As evident in the literature, obesity in this cohort is a growing crisis in cancer care, 22 presenting a risk of co‐morbid conditions and the risk of disease recurrence, which can negatively impact the quality of life 23 . Similar to the literature, 24 breast cancer survivors in our study were highly concerned by their weight gain, reinforcing the demand on the oncology team for the provision of weight management support or referral to a dietitian.…”
Section: Discussionsupporting
confidence: 76%
“…As evident in the literature, obesity in this cohort is a growing crisis in cancer care, 22 presenting a risk of co‐morbid conditions and the risk of disease recurrence, which can negatively impact the quality of life 23 . Similar to the literature, 24 breast cancer survivors in our study were highly concerned by their weight gain, reinforcing the demand on the oncology team for the provision of weight management support or referral to a dietitian.…”
Section: Discussionsupporting
confidence: 76%
“…(23,24) Three studies about patients' preference regarding weight reduction strategies, respectively conducted in overweight or obese adult cancer survivors, patients undergoing or who underwent a knee replacement, and Australian general practice patients, identified that the majority preferred nutrition counselling and specific physical exercise guidance. (20,25,26) One of these studies also concluded that 68% preferred a home-based weight management program. (25) These findings are comparable with our results in which 60.8% was interested in a consultation with a dietician and 57.9% of patients preferred a completely home-based or telerehabilitation program.…”
Section: Weight Reduction Programsmentioning
confidence: 99%
“…(20,25,26) One of these studies also concluded that 68% preferred a home-based weight management program. (25) These findings are comparable with our results in which 60.8% was interested in a consultation with a dietician and 57.9% of patients preferred a completely home-based or telerehabilitation program. Also in our study, 75.3% of the patients preferred a partially or even completely home-based weight reduction program or telerehabilitation program.…”
Section: Weight Reduction Programsmentioning
confidence: 99%